A Comprehensive Review of Psychotherapeutic Treatment of Sexual Addiction. Issue 1 (2nd January 2016) - Garcia, Frederico Duarte; Assumpção, Alessandra Almeida; Malloy-diniz, Leandro; De Freitas, André Augusto Corrêa; Delavenne, Heloise; Thibaut, Florence
ABSTRACT: Psychotherapeutic treatment, alone or in association with pharmacotherapy, has been reported as effective for the treatment of distress and to relieve sexual addiction-associated symptoms such as shame, depression, and anxiety. In this article, the authors review the current literature on psychotherapeutic treatment of sexual addiction. Different psychotherapeutic approaches for the treatment of patients with sexual addiction have been described. Current evidence on efficacy, efficiency and security of psychotherapeutic treatment of sexual addiction is insufficient to guide clinicians in terms of the best techniques and the most appropriate duration of treatment. Evidence is based on uncontrolled studies and case reports. Further research concerning the efficacy and effectiveness of psychotherapeutic approaches for the treatment of sexual addiction is warranted.